Social Support and Job Satisfaction in Kindergarten Teachers: The Mediating Role of Coping Styles - Yang, Ying; Lu, Xiaozhou; Ban, Yongfei; Sun, Ji (Frontiers in Psychology, 2022)
This study explored the relationship between social support and job satisfaction kindergarten in teachers and the mediating role of coping styles in this relationship. A sample of 617 kindergarten teachers (Mage = 25.13 years, SD = 5.66 years) from kindergartens in mainland China completed questionnaires measuring social support, job satisfaction, and coping style. The results showed that social support was positively related to job satisfaction and positive coping style was positively associated with social support and job satisfaction. Furthermore, the results revealed that positive coping style, but not negative coping style, had a mediating effect on the relationship between kindergarten teachers’ social support and job satisfaction. This study provides initial evidence that coping style mediates the link between social support and job satisfaction in kindergarten teachers, and suggests that increasing social support and encouraging positive coping style could improve kindergarten teachers’ job satisfaction.